2015
DOI: 10.1039/c4en00198b
|View full text |Cite
|
Sign up to set email alerts
|

Effect of N-acetyl cysteine coated CdS:Mn/ZnS quantum dots on seed germination and seedling growth of snow pea (Pisum sativum L.): imaging and spectroscopic studies

Abstract: Anthropogenic nanomaterials (ANMs), once produced, will inevitably be present in the environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 25 publications
0
25
0
Order By: Relevance
“…When rice seeds were treated with water-soluble MPA-linked CdSe quantum dots (QDs) at three different concentrations (0.25 mL QDs+1.25 mL H 2 O, 0.5 mL QDs+1 mL H 2 O and 1 mL QDs+0.5 mL H 2 O), the researchers found that there were higher concentrations that blocked germination while the very low concentration of QD solution had no inhibitory effect [ 149 ]. Das et al [ 150 ] investigated the effect of the ultra-small size (<5 nm) N-acetyl cysteine (NAC)-coated core–shell CdS: Mn/ZnS QDots (NAC-QDs) on the seed germination and seedling growth of garden pea. The seeds were soaked for 24 h in different concentrations of NAC-QD (2, 5, 10, 20, 40, 60, 80 and 100 μg mL −1 ), then germinated in Petri dishes containing the test solutions for 5 days.…”
Section: Effects Of Nanomaterials On Seed Germination and Seedlingmentioning
confidence: 99%
“…When rice seeds were treated with water-soluble MPA-linked CdSe quantum dots (QDs) at three different concentrations (0.25 mL QDs+1.25 mL H 2 O, 0.5 mL QDs+1 mL H 2 O and 1 mL QDs+0.5 mL H 2 O), the researchers found that there were higher concentrations that blocked germination while the very low concentration of QD solution had no inhibitory effect [ 149 ]. Das et al [ 150 ] investigated the effect of the ultra-small size (<5 nm) N-acetyl cysteine (NAC)-coated core–shell CdS: Mn/ZnS QDots (NAC-QDs) on the seed germination and seedling growth of garden pea. The seeds were soaked for 24 h in different concentrations of NAC-QD (2, 5, 10, 20, 40, 60, 80 and 100 μg mL −1 ), then germinated in Petri dishes containing the test solutions for 5 days.…”
Section: Effects Of Nanomaterials On Seed Germination and Seedlingmentioning
confidence: 99%
“…For example, Holm oak acorns received little germination benefit by exogenous N (19.6 mg L −1 ), but benefitted only after the second shoot flush [18]. While it has been demonstrated that application of Mn can improve the germination of plants [47], the effects will be determined by the concentration, form, or oxidation state of Mn [48] and the particular plant species. Adding chemical compounds of Mn treatments have the potential to improve the germination of northern red oak and chestnut oak, but suppress the germination of red maple.…”
Section: Discussionmentioning
confidence: 99%
“…Figures 7 and 8 are bar diagrams representing root and shoot lengths obtained from analysis of morphological changes, as shown in Fig. 6 using the literature protocols [32]. We have also assessed chlorophyll contents of the treated seedlings with differently coated Ag NPs and observed (Fig.…”
Section: Resultsmentioning
confidence: 99%